Pavlovian‐to‐instrumental transfer in Anorexia Nervosa: A pilot study on conditioned learning and instrumental responding to low‐ and high‐calorie food stimuli. (6th November 2019) - Vogel, Verena; Dittrich, Marie; Horndasch, Stefanie; Kratz, Oliver; Moll, Gunther H.; Erim, Yesim; Paslakis, Georgios; Rauh, Elisabeth; Steins‐Loeber, Sabine
Abstract: Anorexia Nervosa is characterized by persistent restraint eating despite severe negative consequences and often a chronic course of the disease. Recent theoretical models suggest that abnormalities in reward processing and incentive salience of disorder‐compatible stimuli as observed in addictive behaviours contribute to the development and maintenance of Anorexia Nervosa. The aim of the present study was to investigate the process of the acquisition of food‐related conditioned responses and the influence of conditioned low‐calorie and high‐calorie food stimuli on instrumental responding for different foods. A Pavlovian‐to‐instrumental transfer paradigm and questionnaires on eating disorder psychopathology ( EDE‐Q, EDI‐2 ) were administered to patients with Anorexia Nervosa ( n  = 39) and healthy controls ( n  = 41). Results indicated that patients with Anorexia Nervosa showed deficits of the acquisition of knowledge of the experimental contingencies. Nevertheless, in patients with Anorexia Nervosa and healthy controls instrumental responding for low‐ and high‐calorie food rewards was affected by stimuli conditioned to these rewards; no group differences were observed. Importantly, in Anorexia Nervosa, instrumental responding for low‐calorie food increased with increasing severity of eating disorder psychopathology suggesting weight‐loss directed behaviour. Future studies are warranted to enhance our understanding of deficits of reward‐associated learning and to replicate and extend findings with regard to the impact of conditioned stimuli on instrumental responding. At present, our findings suggest that cognitive treatment interventions might be warranted that challenge dysfunctional beliefs about weight loss. Abstract : Anorexia Nervosa (AN) is characterized by persistent restraint eating despite severe negative consequences. The present study aimed to investigate the role of learning mechanisms as observed in addictive behaviors for the maintenance of AN. We found that conditioned stimuli affected instrumental responding for food rewards and that instrumental responding for low‐calorie food increased with increasing severity of eating disorder psychopathology.